Kajian Literatur: Potensi Rhizobium Dalam Fiksasi Nitrogen Sebagai Solusi Ramah Lingkungan Untuk Peningkatan Kesuburan Tanah - Mendrofa, Putri Khide Talenta; Waruwu, Ardianus Berkat Saleh; Lase, Natalia Kristiani (CV. SINAR HOWUHOWU, 2024)
The development of solutions to improve soil quality and agricultural sustainability is an important concern at this time, land use that is not considered makes the environment polluted and has a major impact on agricultural sustainability. This research aims to review and analyze the potential of Rhizobium in Nitrogen fixation to maintain an environment away from pollution. The research method used is Systematic Literature Review, where various references will be collected and linked into one information. The results stated that the utilization of Rhizobium in the Nitrogen fixation process is an environmentally friendly solution that strengthens and supports sustainable and environmentally friendly agriculture. The research also states that Rhizobium is able to survive in drought and acidic soil conditions even though it disrupts the effectiveness of the Nitrogen fixation process. Further research is needed to identify the effect of Nitrogen fixation by Rhizobium as an environmentally friendly solution and support soil fertility.